The experiences of organizational silence among nurses: a qualitative meta-synthesis - Jingyi Zou; Xiaoxia Zhu; Xue Fu; Xiaojia Zong; Jing Tang; Chunwei Chi; Jinxia Jiang (BMC Nursing)
Abstract Objective A growing body of research shows that the organizational silence among nurses not only affects their job satisfaction and performance but also exacerbates their intention to leave their jobs, posing a threat to the long-term stability of the nursing team. Therefore, the aim of this study was to synthesize existing qualitative research to explore the real experiences of nurses’ organizational silence behavior and gain insight into the motivations and feelings behind it. Design A qualitative review. Data sources A comprehensive search of the following international databases was performed: PubMed, Embase, CINAHL, Psyinfo, Web of Science, Cochrane Library, Medline, and Ovid, as well as Chinese databases such as the China Biomedical Database (CBM), Wanfang Database (CECDB), Chinese National Knowledge Infrastructure (CNKI) and VIP Database. Review methods All articles concerning the experiences of organizational silence among nurses were included after thoroughly searching 12 databases. The meta-synthesis method was employed to integrate and assess the included qualitative research literature, utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to report the review. Two researchers selected and evaluated the relevant literature, which was then analyzed using meta-integration. Results From a total of 12 articles included in the final analysis, 48 primary findings were extracted, forming 3 main themes and following 8 sub-themes: Individual character, Seniority and experience, Defensive silence, Disregardful silence, Acquiescent silence, Prosocial silence, Causing negative effects, and Causing positive effects were the eight sub-themes under these three main themes. Conclusion Nurses’ organizational silence manifests in different ways, and the motivations and experiences behind each form are different. Therefore, when managers observe nurses’ silent behaviors in the organization, they should identify and assess the motivation and degree of silence and then specifically intervene to reduce the silent behaviors to the greatest possible extent. Clinical trial number Not applicable.